2006
DOI: 10.1002/cphc.200600292
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between O2 and SnO2: Oxygen Ionosorption and Spectroscopic Evidence for Adsorbed Oxygen

Abstract: Tin dioxide is the most commonly used material in commercial gas sensors based on semiconducting metal oxides. Despite intensive efforts, the mechanism responsible for gas-sensing effects on SnO(2) is not fully understood. The key step is the understanding of the electronic response of SnO(2) in the presence of background oxygen. For a long time, oxygen interaction with SnO(2) has been treated within the framework of the "ionosorption theory". The adsorbed oxygen species have been regarded as free oxygen ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
313
0
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(347 citation statements)
references
References 114 publications
19
313
0
15
Order By: Relevance
“…The types of oxygen species at the sensor surface are discussed controversially in the literature. There is no spectroscopic evidence for the oxygen interaction with metal oxides (Gurlo, 2006 (Pulkkinen et al, 2001). Other authors expect the double charged atomic ion O 2− to be the predominant species in dry air between 350 and 450 • C, and a competitive adsorption of O − and O 2− around 300 • C (Suematsu et al, 2014).…”
Section: Concept Of Differential Surface Reduction (Dsr)mentioning
confidence: 99%
“…The types of oxygen species at the sensor surface are discussed controversially in the literature. There is no spectroscopic evidence for the oxygen interaction with metal oxides (Gurlo, 2006 (Pulkkinen et al, 2001). Other authors expect the double charged atomic ion O 2− to be the predominant species in dry air between 350 and 450 • C, and a competitive adsorption of O − and O 2− around 300 • C (Suematsu et al, 2014).…”
Section: Concept Of Differential Surface Reduction (Dsr)mentioning
confidence: 99%
“…600°C and for the second at over 800°C. TPD-O 2 studies over SnO 2 have been reported in a few works [17,21,[39][40][41]. The general conclusion is that the course of TPD-O 2 strongly depends on the pretreatment of the catalyst surface preceding the process of desorption.…”
Section: Oxygen Adsorptionmentioning
confidence: 99%
“…21,22 In addition, the conductance in n-type semiconductor oxides is dependent on oxygen partial pressure, and it decreases when the oxygen partial pressure increase (the inverse is valid for p-type semiconductor oxides). 23,24 Based on these fundamentals, sensor measurements were performed to determine the dominant charge carriers for CCTO films prepared by the PPM and to verify the gas sensitivity of the material (sensor characteristics). The gas test was performed with an oxygen concentration at 12% and varying operating temperatures (200 C, 250 C, and 300 C) (see Figure 2).…”
Section: A Gas Sensing Responsementioning
confidence: 99%